REKLAMA
REKLAMA

Liczby rzeczywiste

Działania na potęgach

Jeżeli wyrażenie $\begin{gather*}\frac{\left( \frac{1}{3}\right)^{-2}\cdot3^3\cdot\sqrt{3}}{3^5} \\ \ \\ \end{gather*}$ przedstawimy w postaci $3^x$, to $x$ jest równe
A. $-1$
B. $-2$
C. $-3\frac{1}{2}$
D. $\frac{1}{2}$

Podpowiedź:

Zastosuj prawa działań na potęgach:
$\begin{gather*}a^{-n}=\left(\frac{1}{a}\right)^n \\ \sqrt[n]{a}=a^{\frac{1}{n}} \\ a^r\cdot a^t=a^{r+t} \\ \frac{a^r}{a^t}=a^{r-t}\end{gather*}$
REKLAMA

Rozwiązanie:

$\begin{split}&\frac{\left( \frac{1}{3}\right)^{-2}\cdot3^3\cdot\sqrt{3}}{3^5}=\\
&= \frac{3^2 \cdot 3^3 \cdot 3^{\frac{1}{2}}}{3^5}=\frac{3^{2+3+\frac{1}{2}}}{3^5}=\\
&=\frac{3^{5 \frac{1}{2}}}{3^5}=3^{5 \frac{1}{2}-5}=3^{\frac{1}{2}}
\end{split} $

Odpowiedź:

D.